IMPLEMENTING FINANCIAL MANAGEMENT EARLIER THROUGH SAVING - Renata Hutasoit; Zubaedah Fahmi; Gabriella Buulolo; Tara Putra Utama (International Journal Labs, 2022)
Saving is generally very good behavior and should be inculcated early. Saving is used to prepare a person to have the choice to control their needs and have the choice to anticipate their future. Unfortunately, nowadays we rarely find young people who like to save. Indeed, today's children's interest in saving is very low. Indeed, many advantages can be obtained from saving. Many variables cause children's low interest in saving. One of them is because there is no lack of awareness. This Student Service to the Community (PMKM) aims to build awareness about the importance of setting aside money (saving) for children at the Ishlahul Hayat Foundation, Pondok Petir, Depok through a project to save money. Children at the Ishlahul Hayat Foundation become the object of student service activities to the community because they need attention from external parties to nurture them. This PMKM activity was carried out according to the plan and lasted for one day. This PMKM activity aims to increase awareness for saving children at the Ishlahul Hayat Foundation, Pondok Petir.